Manufacture and characterization of a Bolus composed of water, bi-distilled glycerin, gelatin and formaldehyde - Carlla da Motta Oliveira; Fábio Fernandes Brüning; Jessé Gevezier Prado Lyra; Susan Yamamoto Zanetti; Melissa Funchal; Tatiane Cristina de Oliveira Fernandes (Brazilian Journal of Radiation Sciences)
In years the bolus is used as human tissue compensator in treatments of superficial tumors using photons and electrons in the radiotherapy. In order to obtain a low cost and noncommercial bolus, it is proposed in this work to find an optimized bolus recipe composed of: water, bidistilled glycerin, gelatin and formol. It was manufactured 14 samples and it was evaluated their mass densities, homogeneity and malleability which M and N samples was classified for dosimetric analyses. The percentage depth dose (PDD) curves of M and N samples were measured and compared to the PTW RW3 solid water PDD curve for three energies, 6 MV, 6 MeV and 18 MeV. The PDDs comparisons results showed good agreement and differences smaller than 6% in the percentage depth values for depths smaller than 1,5 cm, except to 6 MeV electron energy which the sample N had difference of 17%. The M sample presented better results for the three measured energies and it was defined as the best recipe to a bolus between the analyzed samples in this work.